Biomechanics of slips after fatigue: Effect of muscular and mental fatigue - Lew, Fui Ling (2016)
Falls are a major safety concern in both daily activities and occupational settings. In Singapore, falls remain as the top incident type for workplace injuries. Falls not only result in accidental injuries on various body parts but also cause deaths and tremendous economic losses. The causes of falls are multi-factorial. The risk factors associated with falls can be classified as environmental factors, task-related factors, and personal factors. Among these risk factors, fatigue (muscular or mental) has been identified as a major task-related risk factor that can lead to falls (Hsiao and Simeonov 2001). Slips are the most common external perturbations that may initiate falls. Many studies have investigated how muscular fatigue affects biomechanics of slips, but most of them focused on the localized muscular fatigue. Most daily/occupational activities involve multi-joint movement. Therefore, multi-joint muscular fatigue is much more common and its effects on biomechanics of slips may be more practically relevant. In addition, it was reported that upper limbs play an important role in recovery from slips. However, nobody has reported the effects of upper-limb fatigue on biomechanics of slips. Further, to our best knowledge, no investigation has been conducted on the effects of mental fatigue on biomechanics of slips. To fill in these research gaps, two studies have been completed in this thesis. The objective of the first study was to investigate the effects of multi-joint muscular fatigue on biomechanics of slips where both lower-limb fatigue and upper-limb fatigue were examined. Sixty healthy young adults participated in the first study, and were evenly categorized into three groups: no fatigue (n = 20), lower-limb fatigue (n = 20), and upper-limb fatigue (n = 20). This is a between-subjects design. The results showed that multi-joint muscular fatigue affects biomechanics of slips in all three phases of slips (i.e. initiation, detection, and recovery). The effects of lower-limb fatigue are more significant than upper-limb fatigue. The objective of the second study was to investigate the effects of mental fatigue on biomechanics of slips. Forty-four healthy young adults participated in the second study, and were evenly categorized into two groups: no fatigue (n = 22) and mental fatigue (n = 22). The experimental protocol was similar with the first study except that mental fatigue was induced to the participants in the mental fatigue group by performing an AX-continuous performance test. The results showed that mental fatigue has adverse effects in all the three phases of slips. In particular, it leads to increased likelihood of slip initiation, poorer slip detection, and a more insufficient reactive recovery response to slips.